Implementasi Digital Game Play Learning (DGPL) di Sekolah Dasar - Septian Mukhlis; Nur Luthfi Rizqa Herianingtyas (PUCUK REBUNG: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2021)
This study aims to describe and interpret the implementation of Digital Game Play Learning (DGPL) in elementary schools. This study used a qualitative approach. The data were collected by using in-depth interviews, participant observation, field notes, and documentation. The data validity was determined through sources and techniques triangulation. The subjects were elementary school teachers in SD IT Nurul A’raaf. The data were analyzed by using Interactive Analysis Model from Miles and Huberman. The results show: 1) the planning of Digital Game Play Learning (DGPL) program has been coordinated by the board of DGPL team. This team was to be responsible for planning, implementing, and evaluating DGPL program; 2) DGPL has been implemented in online class in three phases, namely planning, doing, and reflecting. Besides, DGPL  is oriented to build fun learning based digital game play for teachers and students in the pandemic of covid-19. and 3) the evaluation of DGPL implementation has been conducted by the team who has implemented online class of DGPL thoroughly in intensive discussion of reflection.